Super Priority Destination Mandalika: Quality of Sport Tourism Services: Destinasi Super Prioritas Mandalika: Kualitas Layanan Wisata Olahraga - Satiadji, Amirosa Ria; Ali Muhtasom; Lilik Hidayati; Ardhana, Valian Yoga Pudya; Mohammad Javed Equbal (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2024)
Sports tourism is here to provide added value for the intrinsic and extrinsic elements of destinations in an area which has implications for increasing the number of visitors. In Indonesia, there are several regions that promote sports tourism to boost tourist visits and the regional economy, including NTB Province with Mandalika. Mandalika has now become a super priority destination in NTB Province and the center of attention in the development of sports tourism. To ensure this development runs well, it is necessary to understand the factors that influence the quality of service in this destination. Therefore, this research is needed to assess the quality of sport tourism services in Mandalika. The data collection technique uses scraping and crawling then creates a questionnaire and the results are analyzed using statistical tests. The results of the analysis show that event management has the most significant influence on the perception of service quality at sports event destinations with an influence of 97.7%. Besides that, the importance of event management in improving service quality, destination managers must utilize social media and online advertising as an effective marketing strategy and collaborate with sports influencers to increase tourist interest and participation.